The Phenomenon of Al-Haal in the Book Al-Ghuluwwu wa Atsaruhu fi al-Irhab wa Ifsad al-Mujtama’ Belongs to Al-Sayyid Muhammad bin ‘Alawi al-Maliki al-Hasani (Grammar Study) - Sirfi Fatoni, Ahmad (Universitas Muhammadiyah Sumatera Barat, 2025)
This research reveals the phenomenon of al-haal in the book Al-Ghuluwwu wa Atsaruhu fi al-Irhab wa Ifsad al-Mujtama' by Muhammad bin Alawi al-Maliki al-Hasani. This book is very important in correcting deviant ideas about doctrine and the like. The theory of al-haal is used to reveal the Arabic texts in that book, because al-haal plays an important role in revealing the text deeply and throughly, no matter how insignificant it may be in speech, but its role is significant and enormous. This research is qualitative, and the analysis used is descriptive analysis. The method of data collection is listening, reading, and note-taking, and the other method is the purposive sampling method. All of these methods are used to perform the analysis of this research. The results of this research are as follows: (1) There are 15 examples of the al-haal of isim dhohir; there are 5 examples of the al-haal of jumlah; the researcher didn’t find the al-haal of syibhul jumlah (adverb or prepositional phrase); (2) The al-haal of isim dhohir consists of 6 examples of washfun nakiroh and 9 examples of mashdar nakiroh; the case of jumlah consists of 5 examples of jumlah fi’liyyah; (3) The researcher finds three examples of al-haal al-muta’addidah, that phenomenon exists in Arabic texts and it’s permitted by grammarians. (4) The researcher also finds one example of ‘amil al-haal al-mahzufah, due to the presence of al-haal that confirms the meaning of sentence. (5) During the analysis process, the researcher also finds the ‘amil al-haal from ma’na al-fi’il and its type which is isim isyaroh, and there is one example. The researcher analyzes all of these in a purposive sampling method.